Direct Synthesis and Enhanced Rectification of Alloy‐to‐Alloy 2D Type‐II MoS2(1‐x)Se2x/SnS2(1‐y)Se2y Heterostructures. Issue 8 (14th January 2021) - Wang, Xiaoting; Pan, Longfei; Yang, Juehan; Li, Bo; Liu, Yue‐Yang; Wei, Zhongming
Abstract: The interfacial tunable band alignment of heterostructures is coveted in device design and optimization of device performance. As an intentional approach, alloying allows band engineering and continuous band‐edge tunability for low‐dimensional semiconductors. Thus, combining the tunability of alloying with the band structure of a heterostructure is highly desirable for the improvement of device characteristics. In this work, the single‐step growth of alloy‐to‐alloy (MoS2(1‐ x ) Se2 x /SnS2(1‐ y ) Se2 y ) 2D vertical heterostructures is demonstrated. Electron diffraction reveals the well‐aligned heteroepitaxial relationship for the heterostructure, and a near‐atomically sharp and defect‐free boundary along the interface is observed. The nearly intrinsic van der Waals (vdW) interface enables measurement of the intrinsic behaviors of the heterostructures. The optimized type‐II band alignment for the MoS2(1‐ x ) Se2 x /SnS2(1‐ y ) Se2 y heterostructure, along with the large band offset and effective charge transfer, is confirmed through quenched PL spectroscopy combined with density functional theory calculations. Devices based on completely stacked heterostructures show one or two orders enhanced electron mobility and rectification ratio than those of the constituent materials. The realization of device‐quality alloy‐to‐alloy heterostructures provides a new material platform for precisely tuning band alignment and optimizing device applications. Abstract : The single‐step growth of alloy/alloy (MoS2(1‐ x ) Se2 x /SnS2(1‐ y ) Se2 y ) vertical heterostructures is demonstrated and the heterostructure exhibits a nearly intrinsic van der Waals (vdW) interface in terms of a near‐atomically sharp and defect‐free boundary along the interface as well as a well‐aligned epitaxial relationship. The almost‐ideal interface enables the identification of the intrinsic behavior of the heterostructures such as the band alignment, charge transfer, and carrier transport.